Inconsistencies in the perceived impact of the menstrual cycle on sport performance and in the prevalence of menstrual cycle symptoms: A scoping review of the literature - Oester, C.; Norris, D.; Scott, D.; Pedlar, C.; Bruinvels, G.; Lovell, R. (Journal of Science and Medicine in Sport, 2024)
Objectives This scoping review aimed to summarize the findings of studies regarding the perceived impact of the menstrual cycle on athletic performance, as well as the prevalence of negative menstrual cycle symptoms.